Banking Information Technology on Economic Inequality: An analysis of Electronic Money - Anna Sardiana (Indonesian Journal of Economics, Social, and Humanities, 2021)
The purpose of this study is to analyze and determine the role of banking technology, specifically the use of electronic money in reducing economic inequality in Indonesia. Gini coefficient analysis was used as method in data analysis to measure economic inequality. The data used in the study was secondary data sourced from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The comparison is done using the Gini coefficient calculation method. The results of analysis in this study indicate that there is an increase that causes economic inequality in Indonesia regarding the use of server-based electronic money. The findings in this study also indicate that chip-based electronic money which is a product of banking technology can reduce the level of economic inequality in Indonesia.